A 12, 700-year history of paleolimnological change from an Andean microrefugium. (February 2019) - de Novaes Nascimento, Majoi; Laurenzi, Anne Gail; Valencia, Bryan G; Van, Robert; Bush, Mark
We present a 12, 6700-yr limnological history of Lake Miski, a high-elevation lake in a wet section of the Peruvian Andes. While many shallow Andean lakes dried up during the mid-Holocene, loss-on-ignition, magnetic susceptibility, and diatom analysis showed that Lake Miski was a constant feature in the landscape. Overall, fluctuations in the fossil diatom communities of Lake Miski tracked changes in insolation, but this was not the only mechanism influencing observed variability. We identify periods when insolation and interactions with the Pacific Ocean may have played a role in structuring local climate and diatom assemblages. The true mid-Holocene Dry Event (MHDE) is manifested in this record between 8000 and 5000 cal BP, but the carbonate stratigraphy and the diatom community indicated that although the level of the lake decreased, it never completely dried out, instead there was higher availability of planktic habitat and stronger mixing than in much of the Holocene. High rates of biological change observed during the late-Holocene in other records from Peru associated with human amplification of climatic signals were not observed in Lake Miski, as this lake may have been too wet and remote to be strongly influenced by human activity. Because of the presence of a woodland microrefugium, Lake Miski was suggested to have been an unusually climatically stable and wet location during the regional drying associated with the MHDE. Our new limnological information provides additional insights relating to this discussion. The presence of the observed woodland apparently withstood fluctuations that induced state changes in the lake and diatom flora, underscoring that microrefugia do not equate to 'unchanging' hydrologies or climates.